Detection of circulating tumor cells with CK20 RT-PCR is an independent negative prognostic marker in colon cancer patients – a prospective study. Issue 1 (December 2017) - Hinz, Sebastian; Hendricks, Alexander; Wittig, Amke; Schafmayer, Clemens; Tepel, Jürgen; Kalthoff, Holger; Becker, Thomas; Röder, Christian
Abstract Background Detection of circulating (CTC) or disseminated tumor cells (DTC) has been associated with negative prognosis and outcome in patients with colorectal cancer, though testing for these cells is not yet part of clinical routine. There are several different methodological approaches to detect tumor cells but standardized detection assays are not implemented so far. Methods In this prospective monocentric study 299 patients with colon cancer were included. CTC and DTC were detected using CK20 RT-PCR as well as immunocytochemistry staining with anti-pan-keratin and anti-EpCAM antibodies. The primary endpoints were: Evaluation of CTC and DTC at the time of surgery and correlation with main tumor characteristics and overall (OS) and disease free survival (DFS). Results Patients with detectable CTC had a 5-year OS rate of 68% compared to a 5-year OS rate of 85% in patients without detectable CTC in the blood (p  = 0.002). Detection of DTC in the bone marrow with CK20 RT-PCR was not associated with a worse OS or DFS. Detection of pan-cytokeratin positive DTC in the bone marrow correlated with a significantly reduced 5-year OS rate (p  = 0.048), but detection of DTC in the bone marrow with the anti-EpCAM antibody did not significantly influence the 5-year OS rate (p  = 0.958). By multivariate analyses only detection of CTC with CK20 RT-PCR in the blood was revealed to be an independent predictor of worse OS (HR1.94; 95% CI 1.0–3.7;p  = 0.04) and DFS (HR 1.94; 95% CI 1.1–3.7;p  = 0.044). Conclusions Detection of CTC with CK20 RT-PCR is a highly specific and independent prognostic marker in colon cancer patients. Detection of DTC in the bone marrow with CK20 RT-PCR or immunohistochemistry with anti-EpCAM antibody is not associated with a negative prognostic influence.